Developing Kotak Pintar Cerdas Aksara (Kopica) Media Integrated with Religious Tolerance for Enhancing First-Graders’ Initial Reading Skills - Rosita, Farida Yufarlina; Andita , Putri (Universitas Pendidikan Mandalika, 2025)
The low level of students’ initial reading skills and the urgent need to instill religious tolerance highlight the importance of developing innovative learning media. This study aims to develop KOPICA (Kotak Pintar Cerdas Aksara) to enhance initial reading skills integrated with religious tolerance and to evaluate its validity and practicality. The research applied the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. Expert validation results showed an overall score of 88.3%, while the practicality assessment by teachers and students indicated an average score of 92%. Data analysis using the Paired Samples t-test formula with SPSS 19 revealed a probability value (Sig) of 0.000, which is ≤ 0.05, confirming a significant difference and validating the effectiveness of KOPICA. The novelty of this study lies in the original integration of religious tolerance values into early reading materials, making literacy learning a natural vehicle for character formation from the earliest stages of education. The practical implication is that teachers and curriculum developers can utilize KOPICA as an innovative medium that not only strengthens students’ literacy skills but also fosters tolerant attitudes in daily classroom practices. This dual contribution aligns with the principles of 21st-century learning that emphasize student-centered approaches, while simultaneously preparing students for harmonious social interactions in the future.